2020
DOI: 10.21873/anticanres.14206
|View full text |Cite
|
Sign up to set email alerts
|

Upfront Surgery for Small Intestinal Non-Hodgkin's Lymphoma

Abstract: Background/Aim: The clinical significance of surgery for secondary small intestinal non-Hodgkin's lymphomas (NHL) remains unknown. This study aimed to investigate the efficacy of resection for both primary and secondary small intestinal NHL. Patients and Methods: Twenty patients with small intestinal lymphoma who underwent surgical resection at our Institute between 2009 and 2017 were retrospectively evaluated. The clinicopathological and surgeryrelated factors were reviewed. We also analyzed their surgical ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
(32 reference statements)
0
12
0
1
Order By: Relevance
“…Hong et al conducted an analysis involving 82 patients to explore the effect of surgery in small intestinal lymphoma, which showed that gross resection contributed to the enhancement of progression‐free survival without obviously increasing the risk of complications 21 . A recent study showed that surgery before chemotherapy is an effective and secure treatment for small intestinal NHL, as it can prevent chemotherapy‐related perforation 20,43 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hong et al conducted an analysis involving 82 patients to explore the effect of surgery in small intestinal lymphoma, which showed that gross resection contributed to the enhancement of progression‐free survival without obviously increasing the risk of complications 21 . A recent study showed that surgery before chemotherapy is an effective and secure treatment for small intestinal NHL, as it can prevent chemotherapy‐related perforation 20,43 …”
Section: Discussionmentioning
confidence: 99%
“…Results of GI lymphoma studies are debatable regarding the benefit of surgical excision 3,19 . In recent years, many researchers recommended a combined therapy of chemotherapy and surgery to improve OS 13,20,21 . Due to the potential risk of death and decreased quality of life, the contribution of surgery to PI‐DLBCL needs to be reassessed.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 However, there is strong evidence that initial management with surgical resection followed by adjuvant chemotherapy is associated with increased survival. [21][22][23] In our study, this was the standard strategy for management of patients with small bowel lymphoma.…”
Section: Discussionmentioning
confidence: 97%
“…Con frecuencia, el diagnóstico se hace después de una intervención quirúrgica, cuando se presenta una complicación, siendo las más frecuentes perforación intestinal, obstrucción y sangrado 1,[10][11][12] .…”
Section: Discussionunclassified